Changes in Heart Rate and Blood Oxygen Saturation during Mandibular Third Molar Surgery - Ehsan Aliabadi; Siavash Bagheri (Mashhad University of Medical Sciences, 2020)
Introduction:  Third molar removal surgery is one of the most common oral and maxillofacial operations that sometimes can be complicated and time-consuming. As a result, monitoring the vital signs of a patient during this surgery seems to be crucial. Therefore, the aim of this study was to evaluate heart rate and blood oxygen saturation variations during mandibular third molar surgery. Materials and Methods: This cross-sectional descriptive study was carried out on 50 patients who referred to the Surgery Department of the Dental School of Shiraz University of Medical Sciences, Iran for the surgical removal of the third molar. In this study, the heart rate and oxygen saturation of the participants were measured during eight phases, including when the patients were in the waiting room, sitting on dental chair, regional anesthetic medication was injected, surgeon started incising the gum, during bone removal, third molar extraction, suturing, and at the end of surgery. The data were analyzed by the repeated measures analysis of variance and independent samples t-test P<0.05 was considered statistically significant. Results:Our findings demonstrated that28 (56%) and 22 (46%) of the patients were male and female, respectively. The mean age of participants in this study was 30.12 years. The mean heart rate and oxygen saturation of the subjects during all the mentioned phases were found as 80.52 beats/min and 97.22%, respectively. A significant relationship was observed between the heart rate of the patients (P<0.001) and oxygen saturation in all phases. Conclusion: According to the results of this study, the highest heart rate of the patients under third molar removal surgery was recorded during the local anesthetic injection. Furthermore, oxygen saturation remained in the normal range during this operation.